2011
DOI: 10.1139/o10-024
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the H1 C-terminal domain and function in chromatin condensationThis paper is one of a selection of papers published in a Special Issue entitled 31st Annual International Asilomar Chromatin and Chromosomes Conference, and has undergone the Journal’s usual peer review process.

Abstract: Linker histones are multifunctional proteins that are involved in a myriad of processes ranging from stabilizing the folding and condensation of chromatin to playing a direct role in regulating gene expression. However, how this class of enigmatic proteins binds in chromatin and accomplishes these functions remains unclear. Here we review data regarding the H1 structure and function in chromatin, with special emphasis on the C-terminal domain (CTD), which typically encompasses approximately half of the mass of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 88 publications
(134 reference statements)
1
50
0
Order By: Relevance
“…The lowcomplexity sequence of the CTD, which includes ϳ40% lysine and a significant content of alanine and proline, results in the domain remaining unstructured in aqueous solution due to charge repulsion but acquiring a kinked-helix conformation when bound to DNA (39,40). Interactions with the CTD promote the formation of higherorder chromatin structures as well as increase the residence time (23,37,41). Modeling suggests that a highly charged CTD compacts chromatin more effectively, resulting in silencing, whereas less-charged CTDs promote a chromatin folding in which the genome is more accessible (42).…”
Section: Linker Histonesmentioning
confidence: 99%
“…The lowcomplexity sequence of the CTD, which includes ϳ40% lysine and a significant content of alanine and proline, results in the domain remaining unstructured in aqueous solution due to charge repulsion but acquiring a kinked-helix conformation when bound to DNA (39,40). Interactions with the CTD promote the formation of higherorder chromatin structures as well as increase the residence time (23,37,41). Modeling suggests that a highly charged CTD compacts chromatin more effectively, resulting in silencing, whereas less-charged CTDs promote a chromatin folding in which the genome is more accessible (42).…”
Section: Linker Histonesmentioning
confidence: 99%
“…Although it is not an intrinsic constituent of the nucleosome, the linker histone H1/H5 is an essential molecule that binds to the nucleosome and plays a crucial role in chromatin fiber condensation and cell development [37]. This accessory protein consists of a rigid and well-folded globular head linked to a short N-terminal and a long C-terminal domains, both of which are intrinsically disordered and essential for cell regulation [38].…”
Section: Atomistic Simulations Of Chromatin Componentsmentioning
confidence: 99%
“…Studies have shown that N-terminal domain of the LH does not have significant effect on the higher-order chromatin organization; however, the intrinsically disordered C-terminal domain can be a crucial factor in chromatin architecture [37]. In this context, our refined linker histone model that treats in detail the non-uniform globular head structure as well as the flexible and intrinsically disordered C-terminal domain has captured the dynamic condensation of the C-terminal domain upon binding to the nucleosome (Fig.…”
Section: Simulations Of Oligonucleosomesmentioning
confidence: 99%
“…The middle globular domain preferentially binds to the nucleosome core with one or two DNA linkers (Allan et al, 1980; Singer and Singer, 1976; Zhou et al, 2013). The long C-terminal tail interacts with linker DNA (Caterino and Hayes, 2011; Fang et al, 2012; Lu and Hansen, 2004) and is important for higher affinity binding of linker histones to the nucleosome (Zhou et al, 2013), folding of 30 nm chromatin fibers (Allan et al, 1986), association of linker histones with chromatin in vivo (Brown et al, 2006; Hendzel et al, 2004), and the stem structure formation of longer linker DNA in vitro (Bednar et al, 1998; Hamiche et al, 1996; Syed et al, 2010). …”
Section: Introductionmentioning
confidence: 99%